Venture Capital and Startup Agglomeration - CHEN, JUN; EWENS, MICHAEL (Journal of Finance, 2025)
ABSTRACT This paper examines venture capital's (VC) role in the geographic clustering of high‐growth startups. We exploit a rule change that disproportionately impacted U.S. regions that historically lacked VC financing via a restriction of banks to invest in the asset class. A one‐standard‐deviation increase in VCs' exposure to the rule led to a 20% decline in fund size and a 10% decrease in the likelihood of raising a follow‐on fund. Startups were not wholly cushioned: financing and valuations declined. Startups also moved out of impacted states after the rule change, likely exacerbating existing geographic disparity in entrepreneurship.